Ambon-Maluku Indigenous Knowledge About Tsunami in the Songs Air Turun Naik Di Hutumuri and Banjir Galala - Rizki Nurislaminingsih; Yety Rochwulaningsih; Edwin Rizal (Journal of Music Science, Technology, and Industry, 2026)
Purpose: Tsunami often occurs in Ambon–Maluku so that people know its characteristics. Ambonese share knowledge about it with their social environment through songs. The songs that tell the story are Air Turun Naik di Hutumuri (Water Recedes and Gushes into the Air in Hutumuri) and Banjir Galala (Flood in Galala). This study aimed to explore the Ambonese indigenous knowledge about the tsunami implied in the songs. Method: This research is qualitative with a Content-Driven Document Analysis approach. Result and Discussion: The results showed that the themes of indigenous knowledge about the tsunami in Ambon were signs of nature, the way to self-rescue, and post-disaster situations. The sub-themes of natural signs were bamboo floating in the sea, low tide, and flocks of Talang birds flying around the village. The sub-theme of self-rescue was running to the mountains. The sub-themes of the post-disaster situation described washed away houses, flooding, and disappearing villages. Implication: The findings showed that people also knew other tsunami characteristics: earthquakes, rumbling sounds on the hills, giant black and white waves, loose beach sand, thousands of fish and rocks stranded in the village. Another finding was that the Maluku people's culture carried out activities to manage indigenous knowledge through songs and singing. In conclusion, the songs contain local wisdom about tsunami characteristics (before, during, and after the disaster) and self-rescue.